Superior mesenteric arteriovenous fistula embolisation complicated by bowel ischaemia. (15th May 2013) - Hussein, Maher; Issa, Ghada; Muhsen, Shirin; Haydar, Ali
Abstract : Superior mesenteric arteriovenous fistulas are rare, especially when iatrogenic in origin. Management of these fistulas can be surgical or endovascular. Endovascular embolisation is the preferred modality with a low rate of complications. Among the reported complications, bowel ischaemia is considered an unlikely occurrence. We report a case of a complex iatrogenic arterioportal fistula that was managed by endovascular embolisation and controlled through both its inflow and outflow, and was later complicated by bowel ischaemia.